Penggunaan Monopoli Kartu Bergambar Sebagai Media Peningkatan Pengetahuan Anak Tentang Diare di SDN Sumber 1, Sleman, Yogyakarta - Nur Latifah Sri Maharani; Jenita Doli Tine Donsu; Bondan Palestin (Poltekkes Kemenkes Yogyakarta, 2025)
Diarrhea is a significant public health problem in Indonesia due to high morbidity and mortality rates, especially in the toddler and child age groups. Effective prevention efforts are very important from an early age, especially through increasing the knowledge of elementary school children about this disease. Health education delivered through interesting and fun methods, such as educational games, is believed to be able to increase the effectiveness of learning. This study aims to determine the increase in children's knowledge about diarrhea after being given education using a picture card monopoly game at elementary school. The study used a pre-experimental design with a pretest-posttest one group design approach. The study population was third and fourth grade students with a sample size of 54 respondents obtained through total sampling. Data collection was carried out using a knowledge test instrument measured before and after the intervention. Data analysis used the Wilcoxon test. The results showed that there was a significant increase in the average value of children's knowledge from before (59.5) to after the intervention (78.0), with a value of p=0.000 which indicates a statistically significant difference. The average difference of 18.5 points strengthens the effectiveness of this educational media in increasing children's knowledge about diarrhea. The conclusion of this study is that the use of picture card monopoly game is effective in increasing' knowledge about diarrhea.